Motivation and satisfaction of volunteers for community-based urban agriculture programmes - Ramalingam, Leelanayagi; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin; Ali, Fazlin (Wiley-Blackwell Publishing, 2019)
Urban agriculture means cultivating plants and raising livestock within cities for food and other uses. A Community‐based Urban Agriculture Programme is where people from residential areas get together as volunteers to practise urban agriculture in an empty space within residential areas. However, the programme encounters problems when it is incapable of attracting enough volunteers and retaining them in order to establish a sustainable programme. This study aims to determine the relationship between the dimensions of motivation and satisfaction of volunteers on the Community‐based Urban Agriculture Programme. Data collected from 375 volunteers on the Community‐based Urban Agriculture Programme in Klang Valley, Malaysia were analysed using descriptive analysis, reliability analysis, correlation analysis, and hierarchical multiple regression analysis. It was found that the most significant predictor of Community‐based Urban Agriculture Programme volunteers’ satisfaction was favoured by external factors such as campaigns, support groups, Department of Extension, and community as well as government policy, followed by love of farming, social referents, and values. Therefore, there should be a focus on the above‐mentioned dimensions of motivation in order to enhance the satisfaction of volunteers towards the Community‐based Urban Agriculture Programme.